WORLD EXPERIENCE IN USAGE OF DISTANCE LEARNING TECHNOLOGIES - Irina Aidrous; Ravil R. Asmyatullin (Высшее образование в России, 2016)
The paper considers the global e-learning market trends and discusses the applicability of online courses which are considered to be the best technologies to face the modern lifestyle. The number of students choosing online courses has been rising, which leads to the future increase of online courses offered by universities. The paper analyses as well factors affecting global education market development. The article deals with the issues of the usage of learning management systems (LMS) as a basis to implement online courses.